What benefits do social networks give us? - Aleixandre-Benavent, Rafael; Ferrer-Sapena, Antonia (Anuario ThinkEPI, 2010)
Social networks are a response to our need of communication. There are three types of social networks: those for the general public, for professionals and for scientists. This paper argues that the use of social networking is changing the meaning of the concept of "friend", and that we have to be careful to preserve our public image in these networks. In general purpose networks, personal and professional issues are intertwined, and this is used by some marketing companies. The Web 2.0 collaborative media tools can be used to achieve advances in science, which is essentially collaborative, but this potential use faces a serious drawback because scientists prefer to communicate their work in scientific journals.
Keywords: Social networks; Web 2.0; Professional networks; Generalist networks; Scientific networks.